2012
DOI: 10.1124/dmd.112.045195
|View full text |Cite
|
Sign up to set email alerts
|

Hydralazine As a Selective Probe Inactivator of Aldehyde Oxidase in Human Hepatocytes: Estimation of the Contribution of Aldehyde Oxidase to Metabolic Clearance

Abstract: ABSTRACT:Aldehyde oxidase (AO) metabolism could lead to significant underestimation of clearance in prediction of human pharmacokinetics as well as unanticipated exposure to AO-generated metabolites, if not accounted for early in drug research. We report a method using cryopreserved human hepatocytes and the time-dependent AO inhibitor hydralazine (K I ‫؍‬ 83 ؎ 27 M, k inact ‫؍‬ 0.063 ؎ 0.007 min

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 32 publications
4
64
0
Order By: Relevance
“…However, work performed by Brian Ogilvie's group at Xenotech, LLC indicated hydralazine is a more potent inhibitor of CYP2D6 than first thought, with an IC 50 of 18 mM in hepatocytes using dextromethorphan as a probe substrate and monitoring dextrorphan formation (B. Ogilvie, personal communication). Since the IC 50 of hydralazine for CYP2D6 is similar to the IC 90 obtained for AO by Strelevitz et al (2012), f m(AO) experiments with CYP2D6 substrates should not use hydralazine.…”
Section: In Vitro Considerations To Assess Aldehyde Oxidase Metabolismmentioning
confidence: 69%
“…However, work performed by Brian Ogilvie's group at Xenotech, LLC indicated hydralazine is a more potent inhibitor of CYP2D6 than first thought, with an IC 50 of 18 mM in hepatocytes using dextromethorphan as a probe substrate and monitoring dextrorphan formation (B. Ogilvie, personal communication). Since the IC 50 of hydralazine for CYP2D6 is similar to the IC 90 obtained for AO by Strelevitz et al (2012), f m(AO) experiments with CYP2D6 substrates should not use hydralazine.…”
Section: In Vitro Considerations To Assess Aldehyde Oxidase Metabolismmentioning
confidence: 69%
“…1) (Hutzler et al, 2012). The role of aldehyde oxidase in the production of BIBU1476 was confirmed by a decrease in the observed in vitro clearance in cryopreserved human hepatocytes when the AO-selective inhibitor hydralazine was coincubated (Hutzler et al, 2012), an in vitro phenotyping methodology also reported by Strelevitz et al (2012).…”
mentioning
confidence: 70%
“…Allopurinol has been characterized as a highly selective inhibitor for XO (Panoutsopoulos et al, 2004), and thus, was used to determine whether XO had a significant effect on the oxidation of DACA. In addition, to ensure that the DACA metabolism was mediated exclusively by AO, hydralazine was used as a highly specific inhibitor for AO activity (Hutzler et al, 2011;Strelevitz et al, 2012). Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%